THE STIPULATION OF â€œRETURN OF THE ENDOWMENT OBJECT TO THE DONORâ€™S PROPERTY IN CASE OF NEEDâ€ AS A RESOLUTORY CONDITION IN THE ENDOWMENT CONTRACT A JURISPRUDENTIAL AND LEGAL STUDY Ø¯ÙˆØ±Ù‡51 Ø´Ù…Ø§Ø±Ù‡4 Ø³Ø§Ù„1398 - ?????, ??? ????; ?????, ???? ???; ??????, ????; ?????, ???? (???????? ??????? ?????? ????)
Different opinions have been presented regarding the validity or invalidity of an endowment in which the donor incorporates a condition under which in case of need, the endowment object returns to his property. The opponents of validity of this act either consider it void ab initio or believe that such act is in fact a surrender of property not endowment; since in any situation, endowment must be perpetual and the condition that the object returns to the donor contradicts the essential character of endowment and is against the requirements of endowment contract. The third category consider the endowment and the condition as valid. The origin of all of the above said theories is the issue of ?requirement of perpetuity in endowment contract? and the possibility of incorporating a resolutory condition therein. The present research, after studying the current jurisprudential opinions in this connection and accepting the theory of non-requirement of perpetuity in endowment, has proven the correctness of ?the validity of endowment on condition that the endowment object returns to the donor's property in case of need? and by examining the concept of resolutory condition in law has considered it as applicable to the condition incorporated in endowment contract and the authors believe that based on the theory accepted in Islamic jurisprudence, it is permitted to incorporate a resolutory condition in the endowment contract and  the condition of return of the object to the donor in case of need is its most obvious instance.